Attitudes towards Accountant Profession: Perception of Accounting Students in Aceh Province, Indonesia - Nita Erika Ariani; Fauziah Aida Fitri; Lilis Maryasih (Journal of Accounting Research, Organization and Economics, 2021)
Objective – This study is aimed to examine the perceptions of undergraduate accounting students in choosing the profession as a professional accountant particularly in the context of Aceh Province, Indonesia. Design/methodology – Quantitative research method was used with multinomial logistic regression analysis, which observes students’ perceptions in choosing career as a professional accountant. The population in this study consist of all final year accounting students at major public universities in Aceh, Indonesia, i.e. Faculty of Economics and Business (FEB) Syiah Kuala University Banda Aceh, FEB Malikussaleh University Lhokseumawe, FEB Teuku Umar University Meulaboh and FEB Samudra Langsa University. Final year students are deemed as most relevant samples as at this stage the majority of students may make decisions in choosing the right career for them once they graduate. Results – It was found that of the six variables studied for their influence on the attitudes of accounting students, only the variable of accounting as a career choice affected the perceptions of accounting students in choosing a career as an accounting profession. Limitation/Suggestion – Future research may add students from private universities as samples to observe the comparison of the attitudes of students majoring in accounting. An in-depth interview may also be conducted to gain more meaningful findings.